Efficiency of preparation of «Tantum Verde®» for the prophylaxis of inflammatory complications in the cavity of mouth for patients after realization of operative interventions on parotid and submandibular glands - Tymofeiev Алексей Александрович (Actual Dentistry, 2020)
Purpose: to define efficiency of preparation of «Tantum Verde®» for the prophylaxis of inflammatory complications in the cavity of mouth for patients after realization of operative interventions on parotid and submandibular glands. Methods. An inspection is conducted 64 patients after operative interventions on large salivary glands. Results. It is set On the basis of the inspections got by us, that hygienical care of cavity of mouth by preparation of «Tantum Verde®» for patients after realization of operative interventions on large salivary glands (parotid and submandibular) is a high-efficiency preventive, as compared to traditionally applied. It is objectively wellproven the methods of inspection, that antiseptic preparation of «Tantum Verde®» is used for the rinse of cavity of mouth has the expressed antiinflammatory effect. The side actions of preparation of «Tantum Verde®» we did not educe. Conclusions. It is well-proven the conducted inspections, that preparation of «Tantum Verde®» can be recommended maxillufacial surgeons and tostomatologies for the prophylaxis of inflammatory postoperative complications in the cavity of mouth for patients after the conducted operative interventions on large salivary glands (parotic and submandibular).